1999
DOI: 10.1159/000024203
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cloning of Peanut Allergens, Including Profilin and 2S Albumins, by Phage Display Technology

Abstract: Background: Peanut kernels contain many allergens able to elicit IgE–mediated type 1 allergic reactions in sensitized individuals. Sera from sensitized patients recognize variable patterns of IgE–binding proteins. The identification of the IgE–binding proteins of peanut extract would faciliate improvement of diagnostic and immunotherapeutic approaches as well as development of sensitive test systems for the detection of hidden peanut allergens present as additives in various industrial food products and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
237
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(245 citation statements)
references
References 34 publications
7
237
1
Order By: Relevance
“…Although about 11 peanut allergens have been reported (www.allergome.org), Ara h 1, Ara h 2, and Ara h 3 are classified as the major peanut allergens because they are generally recognized by more than 50% of peanut-allergic patients (Koppelman et al, 2001). Specifically, Ara h 1 and Ara h 2 are recognized by 70% to 90% of patients with peanut allergy (Burks et al, 1995bClarke et al, 1998), and Ara h 3 is recognized by serum IgE from approximately 44% to 54% of different patient populations with a history of peanut sensitivity (Kleber-Janke et al, 1999;Rabjohn et al, 1999).…”
mentioning
confidence: 99%
“…Although about 11 peanut allergens have been reported (www.allergome.org), Ara h 1, Ara h 2, and Ara h 3 are classified as the major peanut allergens because they are generally recognized by more than 50% of peanut-allergic patients (Koppelman et al, 2001). Specifically, Ara h 1 and Ara h 2 are recognized by 70% to 90% of patients with peanut allergy (Burks et al, 1995bClarke et al, 1998), and Ara h 3 is recognized by serum IgE from approximately 44% to 54% of different patient populations with a history of peanut sensitivity (Kleber-Janke et al, 1999;Rabjohn et al, 1999).…”
mentioning
confidence: 99%
“…Other two genes are -Ara h3 isolated at University of Arkansas (Rabjohn et al 1999) and Ara h4 isolated from Borstel, Germany (Kleber-Janke et al 1999) has shown IgE mediated allergic reaction (Kleber-Janke et al 1999;Rabjohn et al 1999). A detailed understanding of the protein structure and diversity is an important prerequisite for attempts to manipulate quality because it indicates the extent to which the structure of the proteins can be manipulated without affecting their biological properties (Shewry and Casey, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The mature proteins are an oligomer of six similar (hexameric) subunits (Badley et al 1975;Shewry et al 1995). Peanut contains multiple seed storage proteins some of the arachins (glycinins) are identified as allergens, which are responsible for triggering IgE mediated allergic reaction (Rabjohn et al 1999;Kleber-Janke et al 1999;Viquez et al 2003;Koppleman et al 2004). High sequence homology of peanut Gly-1 with Ara h3 and Ara h4 suggest that peanut Gly-1 also carry corresponding four IgE binding regions (R1 consists of amino acid residue 42 to 77; R2 consists of amino acid residue 157 to 177; R3 consists of amino acid residue 250 to 288 and R4 consists of amino acid residue 290 to 347 of the peanut Gly-1 protein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has previously been applied successfully to identify allergens from cDNA libraries of Aspergillus fumigatus (5), Cladosporium herbarum (29), peanuts (12), and mites (8) by employing IgE antibodies from patients. Genomic phage surface display libraries of three different Borrelia strains and one mixed library consisting of all three strains were constructed by helper phage superinfection according to a published protocol (2).…”
mentioning
confidence: 99%